Fitness and survival of the fall armyworm, Spodoptera frugiperda (Lepidoptera: Noctuidae) on maize in West Java, Indonesia - Susanto, Agus; Setiawati, Wiwin; Muharam, Agus; Udiarto, Bagus Kukuh; Suganda, Tarkus; Putri, Syifa Nabilah Subakti (Penerbit Universiti Kebangsaan Malaysia, 2024)
An important pest of maize is a new invasive species called Spodoptera frugiperda, also known as the fall armyworm (FAW), causing a considerable economic impact in Indonesia since 2019. This insect has a large host range, a quick generation time at the right temperature, a high rate of reproduction, and a high dispersal capacity. In population ecology and pest management, fitness and survival are crucial. This research was aimed to determine some biological aspects and demographic statistics of three FAW populations (lowland, midland, and highland) in a laboratory setting with 25 ± 2 °C, 75 ± 5% relative humidity, and a 12:12 (L:D) hour photoperiod. Findings indicated no variation in the length of the FAW life stage or its reproductive capacity. Nonetheless, notable variations were noted in the average fecundity of females, with FAW of the highland population laying the most eggs (1242.1 eggs). FAW had the shortest mean generation time (T), the highest intrinsic rate of increase (rm ), the finite rate of increase (λ), and the highest net reproductive rate (R0 ) of the highland population. Overall FAW collected from highland, midland, and lowland can adapt well when brought to a laboratory with a constant temperature at 25 ± 2 °C without detriment to the parameters of the life table. The knowledge gained from this study is crucial for managing FAW because it improves comprehension of its life cycle and adaptability to various altitudes, enabling us to take appropriate action to stop its spread.